Performa fase vegetatif bawang merah persilangan (Allium fistulosum L. x Allium cepa L. var. aggregatum) dengan aplikasi dark septate endophyte - Azmi, Chotimatul; Saadah, Imas Rita; Pinilih, Joko; Faoji, Noor; Ahmadi, Noor Roufiq; Surono, Surono; Karjadi, Asih Kartasih; Soedomo, Prasodjo (Buitenzorg: Journal of Tropical Science, 2024)
Dark septate endophyte (DSE) application on shallot is still quite uncommon. This study investigated DSE application on crossed-shallot (Allium fistulosum L. x Allium cepa L. var. aggregatum) in the highlands of Lembang, West Java, Indonesia. Four treatments (Dendrothyrium sp. strain CPP 1.1.44, Curvularia sp. strain TKC 22, and Cladosporium sp. strain KSP.1 and control) with four replications on crossed shallot were investigated. Fresh weight, number of bulbs, number of pseudo-stems, number of leaves, plant height, pseudo-stem diameter, and leaf diameter were measured at 5, 7, 9, 11, and 13 weeks after planting (WAP). All treatments were freshly picked and weighed at 16 WAP. The results showed that crossed-shallots have different responses among treatments. However, all treatments showed the same response for maximum growth time. The highest values for the number of pseudo-stems, number of leaves, plant height, pseudo-stem diameter, and leaves diameter were reached at 13, 11, 9, 9, and 9 WAP, respectively. All treatments were harvested at 16 WAP, 3–8 weeks longer than shallot parental plants (A. cepa L. var. aggregatum). Applying three DSEs was likely to reduce the number of pseudo-stems from crossing lines of shallots and bunching onions. DSE KSP.1 treatment demonstrated an increase in plant height and the number of bulbs. Meanwhile, TKC 22 treatment showed to increase plant height, pseudo-stem, leaf diameter, and fresh weight.   Keywords: dark septate endophyte, shallot, harvest time, pseudo-stem